Antibiofilm and Antivirulence Activities of 6-Gingerol and 6-Shogaol Against Candida albicans Due to Hyphal Inhibition - Lee, Jin-Hyung; Kim, Yong-Guy; Choi, Pilju; Ham, Jungyeob; Park, Jae Gyu; Lee, Jintae (Frontiers in Cellular and Infection Microbiology, 2018)
Candida albicans is an opportunistic pathogen and responsible for candidiasis. C. albicans readily forms biofilms on various biotic and abiotic surfaces, and these biofilms can cause local and systemic infections. C. albicans biofilms are more resistant than its free yeast to antifungal agents and less affected by host immune responses. Transition of yeast cells to hyphal cells is required for biofilm formation and is believed to be a crucial virulence factor. In this study, six components of ginger were investigated for antibiofilm and antivirulence activities against a fluconazole-resistant C. albicans strain. It was found 6-gingerol, 8-gingerol, and 6-shogaol effectively inhibited biofilm formation. In particular, 6-shogaol at 10 μg/ml significantly reduced C. albicans biofilm formation but had no effect on planktonic cell growth. Also, 6-gingerol and 6-shogaol inhibited hyphal growth in embedded colonies and free-living planktonic cells, and prevented cell aggregation. Furthermore, 6-gingerol and 6-shogaol reduced C. albicans virulence in a nematode infection model without causing toxicity at the tested concentrations. Transcriptomic analysis using RNA-seq and qRT-PCR showed 6-gingerol and 6-shogaol induced several transporters (CDR1, CDR2, and RTA3), but repressed the expressions of several hypha/biofilm related genes (ECE1 and HWP1), which supported observed phenotypic changes. These results highlight the antibiofilm and antivirulence activities of the ginger components, 6-gingerol and 6-shogaol, against a drug resistant C. albicans strain.